2018
DOI: 10.1016/j.ijlp.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing advance directives among psychiatric inpatients in India

Abstract: This study's findings are relevant for India and Western countries alike while generating legislation including patients' perspectives. A majority of patients favoured PADs. Absent insight, severe psychopathology and incomplete recovery may negatively influence the way PADs are completed. Therefore, clinicians must assess patient's capacity to formulate PADs carefully, as capacity may significantly influence patients' views. The timing of when to formulate one's PAD within the illness process may be essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
(11 reference statements)
1
22
0
1
Order By: Relevance
“…Considering resource constraints, clinicians working with people with a psychiatric condition may wish to prioritize psychiatric care planning. This is because fluctuating mental capacity seen during relapses of psychiatric conditions may mean these people still retain the capacity to direct other physical or mental health aspects of their care (Chamberlain, Walsh, & Falkowski, ; Gowda et al, ). In the current state of affairs, the medical system depends on an immediate need for care to justify a meeting between a medical professional and service user.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering resource constraints, clinicians working with people with a psychiatric condition may wish to prioritize psychiatric care planning. This is because fluctuating mental capacity seen during relapses of psychiatric conditions may mean these people still retain the capacity to direct other physical or mental health aspects of their care (Chamberlain, Walsh, & Falkowski, ; Gowda et al, ). In the current state of affairs, the medical system depends on an immediate need for care to justify a meeting between a medical professional and service user.…”
Section: Discussionmentioning
confidence: 99%
“…This act is not specific to mental health but allows individuals with mental capacity to register an advance directive documenting their wishes for medical care (Chu et al, ). Unsurprisingly, systematic reviews of the effectiveness of advance medical directives in Asia are lacking, possibly because the service user demand for such services has been low due to limited awareness (Chu et al, ; Gowda et al, ; Lai, Mohd Mudri, Chinna, & Othman, ; Tay, Chia, & Sng, ).…”
Section: Legislationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study,[ 13 ] conducted in a premier institute, reported that among inpatients about to be discharged, most tended to make greater use of the prescriptive sections of PADs. This study evaluated nearly 200 inpatients who had received acute care and were ready to be discharged in the next couple of days.…”
Section: Research On Psychiatric Advance Directives In Indiamentioning
confidence: 99%
“…Only the MHRB has the powers to amend or overrule the AD. [ 16 ] This would need to be done in a very short time to enable the treatment (24–48 h). There is a dearth of human resources (medical and judicial), economic resources, and collective community efforts in treating PMI.…”
Section: Drawbacks and Recommendation For Amending The Mhca 2017mentioning
confidence: 99%